Learning Style Profiles of Gen Z University Arabic Learners - Kafi, Fina Aunul (Borneo Journal of Language and Education, 2026)
Understanding the learning style profiles of Generation Z Arabic language university students is crucial, as their technology-driven cognitive patterns often misalign with conventional pedagogical approaches, necessitating adaptive strategies to optimize Arabic language learning in higher education. This study aims to investigate the learning style profiles of Generation Z students in Arabic Language Departement of Universitas Al-Falah As-Sunniyah Jember East Java Indonesia. By employing a descriptive statistical design, this research analyzes the distribution and dominance of visual, auditory, and kinesthetic modalities among 48 respondents. The results of this study indicate that the learning style of Generation Z students is significantly oriented toward kinesthetic (mean = 8.00) and visual (mean = 7.56) modalities, while the auditory aspect shows the lowest preference (mean = 6.63). These findings suggest a cognitive shift in digital-native students who prioritize physical engagement and structured visual representation over conventional auditory instructions. The study further identifies that the main obstacles in Arabic learning stem from mismatched pedagogical methods that rely heavily on lecturing. Consequently, this research recommends the integration of multimodal learning strategies, such as interactive infographics and experiential learning activities, to optimize students' memory retention and linguistic competence in the 21st-century educational context.